Corrosion inhibition effects of eco-friendly clarithromycin molecules on aluminium in hydrochloric acid solution via experimental, theoretical and optimization approach - O.D. Onukwuli; I.A. Nnanwube; F.O. Ochili; M. Omotioma; J.I. Obibuenyi (Results in Chemistry)
Corrosion inhibition effect of expired clarithromycin on aluminium in 1 M HCl was examined with weight loss, electrochemical, theoretical and optimization methods. Characterization of the inhibitor was executed with gas chromatography mass spectrometry (GC–MS) and Fourier transform infrared (FTIR) spectroscopy, while optimization of the process was executed with response surface methodology (RSM). The adsorption parameters of the inhibitor on the metal surface were determined while scanning electron microscope (SEM) was deployed to assess the metal’s external morphology. The results from the weight loss study reveal that inhibition efficiency (IE) increased with rise in inhibitor concentration (IC), giving a maximum IE of 87.36 % with IC of 0.9 g/L at 303 K, and reduced with increase in temperature to a minimum value of 65.33 % at IC value of 0.9 g/L at 323 K. FTIR results reveal that the inhibitor contained heteroatoms. Additional analysis with GC–MS indicated that heteroatoms-carrying compounds were contained in the inhibitor. They include methyl-cyclodecane, tetradecane, acetate, hexadecane, 2-methoxy-4-(2-propenyl)- phenol, eugenol, cis-vaccenic acid, 2,4-di-tert-butylphenol, pentadecane, n-hexadecanoic acid, diethyl phthalate, dodecanoic acid, tetradecanoic acid, octadecane, carbonic acid, butyl octyl ester, decyl hexadecyl ester, dibutyl phthalate, among others. Results of adsorption study indicated that Langmuir model fitted best to the experimental results. The potentiodynamic polarization (PDP) results suggest that clarithromycin is a mixed-type inhibitor. Results of the electrochemical impedance spectroscopy (EIS) show Nyquist plot with depressed semi-circle, with an IE of 89.23 %. The density functional theory (DFT) results reveal that expired clarithromycin is an appropriate inhibitor for aluminium corrosion in HCl solution. Optimization by RSM gave an optimum IE of 85.43 %, from which artificial neural network (ANN) predicted improved inhibition efficiency. Overall, clarithromycin demonstrated good efficiency as an inhibitor for aluminium corrosion.